„O nowych, a w swej najgłębszej istocie starych zasadach relacji między Polakami a Imperium”. Na kanwie tekstu i podtekstów rozprawy Jekatieriny Bołtunowej - Barańska, Anna (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2025)
The article reviews a book by Russian scholar Ekaterina Boltunova on the Warsaw coronation of Tsar Nicholas I as King of Poland in 1829 and the memory of the wars between Russia and Poland from the early seventeenth to the early nineteenth century, published in Moscow in 2022 by the Novoye Literaturnoye Obozreniye Publishers in the Historia Rossica series.The article includes an extensive presentation of the book’s content and a polemic against some of Boltunova’s theses and her attempt to reinterpret Polish-Russian relations in the spirit of neo-imperial ideology.
p. 161-186
Summary in English.
Keywords: Warsaw coronation of Tsar Nicholas I; Kingdom of Poland 1815–1830; Polish-Russian relations; political symbolism; politics of memory; Poland - relations - Russia - 19th c.; Russia - relations - Poland - 19th c.; Nicholas I (Emperor of Russia; 1796-1855) - coronation